MAKNA ORNAMENTASI PAPANTUNAN DALAM TEMBANG SUNDA CIANJURAN - Denden Setiaji (Prodi Pendidikan Sendratasik FKIP UMTAS, 2019)
This article is an analysis of the meaning of ornamentation found in Sunda Cianjuran songs, especially wanda papantunan, where the role of ornamentation in papantunan has meanings and values ??that can describe the pattern of life or frame of mind of Sundanese society during the formation of Sunda Cianjuran song wanda papantunan, it is expressed through the form of ornamentation and graphic notation presented in each verse and ornamentation to the application of notation. All aspects listed there have values ??that describe the rational pattern of a harmonious and religious Sundanese society.